IMPROVING TEACHERS' ABILITY TO OPERATING ZOOM MEETING AS A DISTANCE LEARNING MEDIA THROUGH CLUSTER-BASED ASSISTANCE AT SMK NEGERI 2 MOJOKERTO - Ahmad Muklason (Jurnal Scientia, 2022)
The background to the problem raised in this school action research (PTS) is the low competence of teachers in using the zoom meeting application for distance learning in implementing learning policies during the Covid-19 pandemic. Meanwhile, one of the teacher's tasks is to carry out creative and innovative learning in order to achieve maximum learning objectives under any conditions. The purpose of this research is to increase teacher competence using the zoom meeting application in distance learning through cluster-based assistance at SMK Negeri 2 Mojokerto City semester 1 of the 2021/2022 academic year. The research method used was school action research (PTS) with two implementation cycles for each cycle covering the stages of planning, implementing, observing and reflecting. The results showed that in the first cycle, teacher competence reached 50%, from the previous pre-cycle only 30% were in the competent category. Meanwhile, in cycle II, 70% of teachers were competent, thus achieving an indicator of research success, namely 70% of all teachers. Based on the results of this study, it was concluded that at SMK Negeri 2 Mojokerto City semester 1 of the 2021/2022 academic year , teacher competence in using the zoom meeting application for distance learning through cluster-based assistance can increase.